Effect of the Pesticide Endosulfan and Two Different Biostimulants on the Stress Responses of Phaseolus leptostachyus Plants Grown in a Saline Soil - Anbu Landa-Faz; Sara González-Orenga; Monica Boscaiu; Refugio Rodríguez-Vázquez; Oscar Vicente (Agronomy, 2021)
Soil salinity and the indiscriminate use of agrochemicals has significantly reduced the productivity of the ‘Chinampas’ agroecosystem in Mexico City. Crop improvement under these stressful conditions may be achieved by soil bioremediation. In this study, we checked the effects of the organochlorine pesticide endosulfan and bioremediation with Penicillium crustosum or a citric waste on the growth of Phaseolus leptostachyus plants in saline soil from the Chinampas area. Biochemical markers associated with specific stress responses were also determined after one month of growth in the different substrates. Plant growth was stimulated by bioremediation of the soil. Both biostimulants reduced the degree of stress affecting the plants, as shown by the increase in photosynthetic pigments and the reduction of proline, malondialdehyde (MDA), and H2O2 contents, and the activation of antioxidant systems. However, the biostimulants appeared to mitigate oxidative stress through different mechanisms. Endosulfan contamination inhibited seed germination—which was reverted to control values in the presence of the biostimulants—and further decreased plant growth. No clear patterns of variation of biochemical stress markers were observed combining endosulfan and the biostimulants. In any case, bioremediation with P. crustosum and/or citric waste is recommended to improve the germination and growth of P. leptostachyus plants.